PELATIHAN FOTOGRAFI DASAR SEBAGAI MEDIA VISUAL PROMOSI WISATA INDONESIA TIMUR - Wegig Murwonugroho (Jurnal AKAL : Abdimas dan Kearifan Lokal, 2020)
Photography is an activity cherised by many people of all age as hobby. In an era with easy access to internet and social media, photography also enjoys an increase in popularity. Young adult age group is the one who benefits the most from those technology advancements. It’s as if they compete to create images on social media to be liked by other people. However, sometimes people lacking in technological knowledge buy cameras without knowing the full technical functions and differences in image quality produced by them. The lack of knowledge in photography basic techniques and aesthetical composition may cause picture quality to suffer. This Program Pengabdian kepada Masyarakat (PkM) with the theme of Photography Basic Training aims to grow basic photography skills as a tool to produce interesting stock photos. Therefore, participants will have the capability to capture the exoticism of East Indonesia, where they come from. Tourist promotion with easthetically pleasing photos is believed to be positively impacting visitor numbers. It’s true that informations about photography basic techniques are prevalent online, but people who are only beginning to learn still need face-to-face guidance to assure transfer of informations occur the right way. After engaging in this PkM program, their knowledge and skill of basic photography techniques will improve. They will be more knowing of how to make more interesting pictures.